Proceedings 2003 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS 2003) (Cat. No.03CH37453)
DOI: 10.1109/iros.2003.1249636
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a 3-D map of rubble by teleoperated mobile robots with a motion canceling camera system

Abstract: In order to search and rescue the victims in rubble effective/): a 3-0 mop of the rubble is required. As a part of the national project of rescue mbot qstem, we are inuestigating a method for constructing a 3-0 map of rubble by teleoperated mobile mbots. We are also planning to build an intuitive user interface for teleoperating robots and navigating in a virtualized rubble modelusing the obtained 3-0 model. In this paper; some preliminary research results are intmduced. We did some design studies of laser ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Communication dropouts between the robots are an important concern in these environments, and as a result, maintaining and enhancing connectivity has become a focused research area (Hsieh et al., ; Tardioli et al., ). Furthermore, the difficult task of robots using onboard sensors to map and localize themselves in these unknown and cluttered environments is being addressed through the integration of various simultaneous localization and mapping (SLAM) methods including using an extended information filter algorithm (Ellekilde et al., ), an extended Kalman filter method (Yokokohji et al., ), and a hybrid SLAM approach (Pfingsthorn et al., ). This section focuses on providing a detailed overview of the related work on human‐robot cooperation and multirobot coordination strategies for USAR applications.…”
Section: Related Workmentioning
confidence: 99%
“…Communication dropouts between the robots are an important concern in these environments, and as a result, maintaining and enhancing connectivity has become a focused research area (Hsieh et al., ; Tardioli et al., ). Furthermore, the difficult task of robots using onboard sensors to map and localize themselves in these unknown and cluttered environments is being addressed through the integration of various simultaneous localization and mapping (SLAM) methods including using an extended information filter algorithm (Ellekilde et al., ), an extended Kalman filter method (Yokokohji et al., ), and a hybrid SLAM approach (Pfingsthorn et al., ). This section focuses on providing a detailed overview of the related work on human‐robot cooperation and multirobot coordination strategies for USAR applications.…”
Section: Related Workmentioning
confidence: 99%
“…To save victims and to mitigate losses when a disaster occurs, rescue robots have been widely researched throughout the world (1) - (13) . In large-scale disaster sites, professional rescuers are insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…In the practical use, the range finder is mounted on the mobile robot whose position cannot be measured directly when the robot is inside rubble. We are investigating a method to estimate the position of robot in the SLAM framework [11]. The method of extracting the environmental features for the SLAM from the picture captured by the NTSC camera is also studied in the research.…”
Section: B Map Building By Online Measurementmentioning
confidence: 99%
“…Experimental results showed that the actual To build a 3D map, the position information of the range finder is needed. We are investigating a method to estimate the position of robot in the SLAM framework [11]. The method of extracting the environmental features for the SLAM from the picture captured by omnivision camera is also studied in our research project of position estimation.…”
Section: Introductionmentioning
confidence: 99%